-5126 =-6-5(x+22)^(5/3)

### 1 Answer | Add Yours

We'll shift -6 to the left side:

-5126+6 = - 5(x+ 22)^(5/3)

-5120 = 5(x+ 22)^(5/3)

We'll divide by -5 both sides:

1024 = (x+ 22)^(5/3)

We'll raise both sides to 3/5 power:

1024^(3/5) = x+22

We'll use the symmetric property and we'll subtract 22 both sides:

x = 1024^(3/5) - 22

x = 2^(10*3/5) - 22

x = 2^6 - 22

x = 64 - 22

x = 42

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes